RESUlTS OF COMPARATIVE FISHING TRIALS WITH RECTANGULAR FlAT AND RECTANGULAR CURVED OTTER BOARDS - DESHPANDE, S D; SIVAN, T M; RAMARAO, S V. S. (Fishery Technology, 2025)
Rectangular flat and rectangular curved otterboards were tested under identical conditions and their relative efficiency ascertained on the basis of catch landed by 137m four-seam shrimp otter trawl. During the study, significant increase was observed in the catch when the gear was rigged with curved otterboards. The horizontal spread berween rectangular otterboards was found to be more by 13% nd they also offered about 10% more towing resistance than the convent ional boards. The otter boards were tested under trawling speed of 2 knots per hour.